Pulmonary cryptosporidiosis and immune reconstitution inflammatory syndrome: a case report and review. (April 2013) - Sullivan, T; Reese, L; Huprikar, S; Lee, M
Summary: Cryptosporidium rarely affects the lungs, and is not typically associated with the immune reconstitution inflammatory syndrome (IRIS). We describe the first published case of pulmonary IRIS following the initiation of antiretroviral therapy in a patient with AIDS and pulmonary cryptosporidiosis, and discuss its implications for HIV patient care.